Dampak Pendidikan Agama Katolik Terhadap Perilaku Siswa SMA Negeri di Kota Pontianak - Martinus Martinus; Amadi Amadi (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2021)
The background of this research is to reveal the impact of Catholic Religious Education on student behavior in Public Senior High Schools in Pontianak City. The purpose of this study was to describe the role of Catholic Religious Education on student behavior in public high schools in Pontianak City; as well as to find out that Catholic Religious Education has a positive or negative impact on student behavior in Public High Schools in Pontianak. This research uses qualitative methods with descriptive research type. Meanwhile, the research subjects were students and teachers of PAK at SMA Negeri Pontianak. Data collection techniques in the form of interview techniques and observation. The results of the study found that Catholic Religious Education at Public Senior High Schools in Pontianak City had a positive impact on student behavior if in the teaching and learning process the teacher really understood their function as PAK teachers. In conclusion, teaching actions by teachers based on love have a positive impact on student behavior in the school, family, and community environment. The implication of the findings of this study is that students behave politely and kindly to everyone.